ANALISIS FINANCIAL DEEPENING DI INDONESIA - Dede Ruslan (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
This paper aims to analize the financial deepening on Indonesia economy. The focusof analysize is to identifiying effect of interest rate, exchange rate and Gross DomesticProduct (GDP) to financial deepening on Indonesian economy for 1980-2007. Methodeof analysize is linier regression model. The result of analysize are Gross DomesticProduct (GDP) and interest rate have significant effect to financial deepening onIndonesian economy.Keywords : financial deepening, linier regression model, gross domestic product